2022
DOI: 10.1080/21655979.2021.1996507
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long non-coding RNA 00960 promoted the aggressiveness of lung adenocarcinoma via the miR-124a/SphK1 axis

Abstract: Long non-coding RNAs (lncRNAs) are closely associated with the development of lung adenocarcinoma (LADC). The present study focused on the role of LINC00960 in LADC. miRNA and mRNA expression levels were detected using quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Cellular functions were evaluated by MTT, colony formation, and Transwell assays, respectively. LINC00960 Luciferase and RNA pull-down assays were performed to clarify the interaction between miR-124a and LINC00960 or Recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…12 In lung adenocarcinoma (LADC), LINC00960 mediated the miR-124a/ sphingosine kinase 1 axis to induce LADC development by promoting cell proliferation, migration, and invasion. 22 We obtained similar outcomes, that is, LINC00960 silencing impeded PC cell proliferation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…12 In lung adenocarcinoma (LADC), LINC00960 mediated the miR-124a/ sphingosine kinase 1 axis to induce LADC development by promoting cell proliferation, migration, and invasion. 22 We obtained similar outcomes, that is, LINC00960 silencing impeded PC cell proliferation.…”
Section: Discussionsupporting
confidence: 62%
“…Another study showed that LINC00960 accelerated cell growth and metastasis in PDAC by inhibiting the miR‐146a‐5p / IRAK1 axis 12 . In lung adenocarcinoma (LADC), LINC00960 mediated the miR‐124a /sphingosine kinase 1 axis to induce LADC development by promoting cell proliferation, migration, and invasion 22 . We obtained similar outcomes, that is, LINC00960 silencing impeded PC cell proliferation.…”
Section: Discussionsupporting
confidence: 55%
“…LINC00960 bears closer potential binding sites with miR-183-5p than Nrdp1 ( Figure 3 A). A few miRNAs have been reported to be targeted by LINC00960 [ 18 21 ] , but LINC00960 bears the highest score to complement miR-183-5p ( ). Several lncRNAs or circRNAs have also been shown to target miR-183-5p [ 22 28 ] , but LINC00960 ranks at the top among all these noncoding RNAs ( ).…”
Section: Resultsmentioning
confidence: 99%
“…lncRNA PVT1 in exosomes promotes osteosarcoma growth and metastasis by sponging miR-183-5p [24] . LINC00960 was found to play an active role in promoting the malignant behaviors of bladder cancer cells [59] , pancreatic ductal adenocarcinoma [19] , lung adenocarcinoma [18] , and osteosarcoma [60] . Interestingly, LINC00960 was also shown to promote lung adenocarcinoma by sponging miR-124a, the latter of which suppresses the expression of SphK1 [18] and regulates cell viability, migration and invasion in pancreatic ductal adenocarcinoma by modulating miR-146a-5p, which targets interleukin 1 receptor-associated kinase 1 [19] .…”
Section: Discussionmentioning
confidence: 99%
“…The complexes were then incubated with Streptavidin agarose beads (Invitrogen) for 1 h at 37°C. The beads were washed, and RNA level were analyzed by qRT-PCR [ 29 ].…”
Section: Methodsmentioning
confidence: 99%